2015
DOI: 10.1007/s10340-015-0679-6
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the behavioral basis for an attract-and-kill strategy to manage the invasive Halyomorpha halys in apple orchards

Abstract: Halyomorpha halys (Stål), the brown marmorated stink bug, is an invasive, polyphagous insect that causes serious economic injury in particular to specialty crops in the United States. Growers have been forced to respond by increasing the frequency of broad-spectrum insecticide (e.g., neonicotinoid, pyrethroid, and carbamate) applications. One strategy to reduce reliance on insecticides is known as ''attract-and-kill'' whereby the targeted insect is attracted to a spatially precise location to be eliminated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 50 publications
7
90
1
1
Order By: Relevance
“…Moreover, the UV source was also used as an insect lure, as preliminary laboratory trials showed an unsatisfactory performance of pheromones/semiochemicals in rearing cages. In fact, BMSB has a too large of an arrestment area around an attractive source (2.5 m around a pheromone source) to be applied in the laboratory (Morrison et al., ). No food source or water was provided in the cages during tests, to standardize and avoid any interference of the attract‐and‐kill unit.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the UV source was also used as an insect lure, as preliminary laboratory trials showed an unsatisfactory performance of pheromones/semiochemicals in rearing cages. In fact, BMSB has a too large of an arrestment area around an attractive source (2.5 m around a pheromone source) to be applied in the laboratory (Morrison et al., ). No food source or water was provided in the cages during tests, to standardize and avoid any interference of the attract‐and‐kill unit.…”
Section: Methodsmentioning
confidence: 99%
“…baited trap compared with plants at 5 and 10 m (Leskey and Hogmire 2007). Additionally, significantly more Halyomorpha halys (Stål), Euschistus spp., C. hilaris , and N. viridula adults were captured in a centrally baited (lure with aggregation pheromone of H. halys and synergist) trap compared with those captured in nonbaited traps 2.5 m from the baited one; trap capture was not significantly different for nonbaited traps 2.5, 5, and 10 m from the baited trap (Morrison et al 2016). …”
Section: Methodsmentioning
confidence: 99%
“…The number and density of adults from trap catches during fall (13 reports; 5 were >50 insects) were far greater than those generated in spring (3 reports of individual insects) and summer (5 reports; none were >50 insects). It has been previously noted that all BMSB life stages are attracted to the pheromone season-long [61]. Our observations of increasing numbers and catch density during fall can probably be explained either by a rising population, or that BMSB sensitivity might be higher during this season, given that their ability to aggregate in suitable shelters during that period directly affects their winter survival.…”
Section: Seasonal Phenology Of Bmsbmentioning
confidence: 50%
“…The overlap between these two notions is particularly alarming, given the ubiquity of late-season apple orchards throughout the Trentino territory, raising the need to control this pest before harvest time to minimize losses. A possible means of control would be the exploitation of the behavioral ecology of this insect, through the adoption of a border-based attract-and-kill technique [61]. The latter enhances the strong 'edge-effect' exhibited by BMSB (the tendency to inhabit trees at the orchard perimeter), by baiting select border row trees with pheromone traps, and subsequently treating them with effective insecticides.…”
Section: Menace In Agricultural Areasmentioning
confidence: 99%